Effectiveness of an applied high intensity interval training as a specific operative training (2019)
The psychophysiological response due to stress of soldiers in actual combat operations have been determined by recent researchers, but there is a lack of knowledge about the most effective training methodologies to prepare these population for these new psychophysiological and tactical requirements. The aim of this study was to analyze the effect of an operative high intensity interval training (HIIT) in the psychophysiological response and shooting performance of professional soldiers. We analyzed 20 soldiers of the Spanish Army which performed an operative HIIT composed by 3 series of 7 repetitions of exercises based on operative military procedures with 30 s of workload and 30 s of resting between repetitions and 5 min resting between series. Blood lactate, rate of perceived exertion and stress, upper and lower limbs, and respiratory muscle strength, skin temperature, blood oxygen saturation, heart rate, cortical arousal, short-term memory and anxiety response were measured before and after the training. After the training rated of perceived exertion and stress, leg strength, heart rate and lactate presented a significant increase and blood oxygen saturation and cortical arousal significantly decreased. An operative HIIT achieves similar psychophysical response than the evaluated in combat simulations in professional soldiers, producing a decrease in cortical arousal and lactate values over the anaerobic threshold.